Effect of prebiotic, probiotic and synbiotic on performance of layers and cholesterol content of egg yolk - Tang, Shirley Gee Hoon; Sieo, Chin Chin; Kalavathy, Ramasamy; Saad, Wan Zuhainis; Wong, Hee Kum; Ho, Yin Wan (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
This study evaluated the effects of prebiotic, probiotic and synbiotic on the performance of laying hens and the cholesterol contents of their egg yolks. One hundred and sixty Hisex Brown hens, aged 20 weeks old, were randomly assigned to four dietary treatments: basal diet (control), basal diet + prebiotic, basal diet + probiotic, and basal diet + prebiotic + probiotic (synbiotic). The results showed that there were no significant differences (P>0.05) among the treatments in the feed intake, feed efficiency, egg mass, egg production and egg weight of 20-27 weeks old layers. However, at 28-35 weeks old, these parameters improved significantly (P<0.05) in the prebiotic-, probiotic- and synbiotic-fed hens compared to the control hens. The egg yolk cholesterol content of the prebiotic-, probiotic- and synbiotic-fed hens were significantly (P<0.05) lower than that of the control hens at 27 weeks of age, but there were no significant differences (P>0.05) among treatments at 35 weeks of age. This study showed that prebiotic, probiotic or synbiotic improved the performance of layers from 28-35 weeks of age and reduced egg yolk cholesterol at 27 weeks of age.